Technology Integration in Community Nursing: Opportunities and Challenges - Jasmin Ambas; Rahaju Ningtyas; Naela Mikyalul Faiza; Nurul Fadhilah (Oshada, 2024)
The integration of technology in community nursing has brought about significant changes in the way health services are delivered. The background to this research is the increasing use of information and communication technology, such as telehealth, telemedicine, and mobile health applications, which have been proven to increase the accessibility and efficiency of health services. However, this process also faces various challenges, including the digital divide, data security and privacy issues, and the need for health workers to adapt to new technologies. The aim of this research is to identify the benefits and challenges of technology integration in community nursing and provide recommendations for improving the quality and accessibility of health services. The research method used is a literature study, where various sources of information from scientific journals, books, research reports and related documents are analyzed in depth to gain a comprehensive understanding of this topic. Research results show that technology has provided various benefits, such as increased access to health services, efficiency in managing patient data, and more coordinated care. However, challenges such as the digital divide, data security and privacy, and adaptation of the health workforce still need to be overcome. Continuous training and strong organizational support are needed to ensure health workers can operate technology well and make optimal use of it. The implications of these findings include the need for strict regulations and advanced security technologies to protect patient data, as well as the importance of involving communities in the technology introduction process to increase social and cultural acceptance of health technologies.